Human Adaptation in Ancient Mesoamerica : Empirical Approaches to Mesoamerican Archaeology - French, Kirk D.; Gonlin, Nancy (Book collections on Project MUSE., 2015)
"From the hydrological engineering behind Teotihuacan's layout, to the complexities of agriculture and sustainability in the Maya lowlands, to the nuanced history of abandonment along different lineages and households in Maya centers, Human Adaptation in Ancient Mesoamerica covers a diverse array of topics which explore human adaptation in Mesoamerica to social, political, economic, and environmental factors"--